Pivmecillinam compared to other antimicrobials for community-acquired urinary tract infections with Escherichia coli, ESBL-producing or not – a retrospective cohort study - Jansåker, Filip (Infect Drug Resist, 2019)
OBJECTIVES: To compare the therapeutic effect of pivmecillinam and other common oral antibiotics for community-acquired urinary tract infections (UTIs) caused by Extended Spectrum Beta-Lactamase (ESBL)- or non-ESBL-producing Escherichia coli. METHODS: Retrospective cohort study from 2010 to mid-2016 with data from the regional Laboratory Database and three national databases on antibiotic prescriptions, hospital admission, and mortality, respectively. Primary care patients (≥18 years) empirically treated for UTI caused by non-ESBL- or ESBL-producing E. coli (non-ESBL and ESBL E. coli) were included. Seven antibiotics, commonly used empirically for UTI, were investigated. Treatment failure measured as the redemption of a new antibiotic prescription or admission to hospital due to UTI. Cox proportional hazard ratios and adjusted risk differences along with 95% confidence intervals were calculated for 14 and 30 days, respectively. RESULTS: Thirty-six thousand two hundred and ninety-three (95.7%) and 1624 (4.3%) cases were included in the non-ESBL and ESBL groups, respectively. Male sex, high age, ESBL production, and resistance to empirical therapy were found to independently increase the risk of treatment failure. Compared to pivmecillinam, ciprofloxacin had significantly lower treatment failure for non-ESBL E. coli, but significantly higher treatment failure in ESBL E. coli. There was no significant difference between nitrofurantoin and pivmecillinam. CONCLUSION: All antibiotics seem to have a higher risk of treatment failure for UTI caused by ESBL-producing E. coli as compared to non-ESBL-producing E. coli. At present, nitrofurantoin and pivmecillinam seem to be the most relevant orally available therapies for E. coli UTI. Local resistance data should guide which of the two that should be the contemporary first-line option.